Forage Mass and Leaf Area Index in Multispecies Pastures Under Continuous Stocking (Boletim de Indústria Animal, 2022)
The association of different species in a pasture ecosystem is a challenge for grazing management, where the leaf area index (LAI) is the end result of interactions between plant-animal-environment. Therefore, this study evaluated the effects of grazing management strategies (GMS) considering forage canopy heights on forage mass production (FM) and LAI in multispecies pastures. The experiment was conducted at the Instituto of Zootecnia in Nova Odess, SP in autumn (June 2021) and spring (December 2021). Multispecies pastures were composed of aruana grass (Megathyrsus maximum cv. Aruana) and a mix of forage legumes: calopo (Calopogonium mucunoides), macrotyloma (Macrotyloma axillare) and stylo (Stylosanthes macrocephala+ Stylosanthes capitata). The study was conducted in four randomized blocks with four treatments (grazing management strategies €“ GMS: 15, 30, 45 and 60 cm canopy heights) and four replications (500 m²/each paddock), with continuous stocking of sheep. For the FM evaluation, the forage was cut at soil level in three 0.25 m² areas, representative of the average paddock height. The samples were weighed, homogenized and divided into two subsamples for component separation and total dry matter quantification after drying in a forced-air oven at 65 °C for 72 hours. The leaf area (cm²) was determined using a LI-COR model 3100 measuring device to calculate the total covered soil area (m²) and to find the LAI values for aruana grass (LAIaruana), legumes (LAILeg) and aruana grass + legumes (LAITotal). Analysis of variance was performed by SAS software using proc MIXED. The Tukey test was applied for comparison of means (P